Optimal Photovoltaic Array Configuration under Non-Uniform Laser Beam Conditions for Laser Wireless Power Transmission - Mou, Zhiqiang; Zhao, Bangbo; Zhu, Lihong; Wang, Jun; Deng, Guoliang; Yang, Huomu; Gou, Yudan (Photonics, 2024)
In a long-distance wireless power transmission system with a non-uniform distribution of laser irradiation, it will significantly reduce the output power of the photovoltaic array, resulting in a large amount of power loss in the system and a decrease in conversion efficiency. This paper proposes an efficient and reliable optimal circuit connection algorithm for the 5 × 5 scale photovoltaic array. Under the laser illumination of 300 W, a 20 m wireless power transmission experiment was performed on four 5 × 5 scale photovoltaic arrays. The results show a 56.49% increase in the maximum output power of the 5 × 5 scale photovoltaic array.